Early posttreatment assessment of MRI perfusion biomarkers can predict long-term response of lung cancer brain metastases to stereotactic radiosurgery - Taunk, Neil K (Neuro Oncol, 2018)
BACKGROUND: Imaging criteria to evaluate the response of brain metastases to stereotactic radiosurgery (SRS) in the early posttreatment period remains a crucial unmet need. The aim of this study is to correlate early (within 12 wk) posttreatment perfusion MRI changes with long-term outcomes after treatment of lung cancer brain metastases with SRS. METHODS: Pre- and posttreatment perfusion MRI scans were obtained in patients treated with SRS for intact non–small cell lung cancer brain metastases. Time-dependent leakage (K(trans)), blood plasma volume (Vp), and extracellular extravascular volume (Ve) were calculated for each lesion. Patients were followed longitudinally with serial MRI until death, progression, or intervention (whole brain radiation or surgery). RESULTS: We included 53 lesions treated with SRS from 41 total patients. Median follow-up after treatment was 11 months. Actuarial local control at one year was 85%. Univariate analysis demonstrated a significant difference (P = 0.032) in posttreatment K(trans) SD between patients with progressive disease (mean = 0.0317) and without progressive disease (mean = 0.0219). A posttreatment K(trans) SD cutoff value of 0.017 was highly sensitive (89%) for predicting progressive disease and no progressive disease. Early posttreatment volume change was not associated with outcome (P = 0.941). CONCLUSION: Posttreatment K(trans) SD may be used as an early posttreatment imaging biomarker to help predict long-term response of lung cancer brain metastases to SRS. This can help identify patients who will ultimately fail SRS and allow for timelier adjustment in treatment approach. These data should be prospectively validated in larger patient cohorts and other histologies.